Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) - Alexandre, Anne (PANGAEA, 2025)
The triple oxygen isotope compositions of precipitation, groundwater and soil water, plant water and phytoliths, monitored between 2017 and 2021 at three sites in Benin and Senegal are presented. The sites are part of the long-term eco-hydro-meteorological observatory for West Africa AMMA-CATCH (Multidisciplinary Analysis of the African Monsoon - Coupling the Tropical Atmosphere and the Hydrological Cycle) (https://www.amma-catch.org/). The data have been used to highlight the contribution that triple oxygen isotope composition can make to trace the present and past water cycle at the soil-plant-atmosphere interface (Alexandre et al., 2025) in the frame of the HUMI-17 project funded by the French national research agency (ANR-17-CE01-0002-01).
Keywords: phytolith; plant water; precipitation; soil water; triple oxygen isotopes; West Africa